Achieving Competitive Advantage Through Digital Transformation and Supply Chain Competence: Evidence from West Java SMEs - Raden Marsha Aulia Hakim; Erna Maulina; Ratih Purbasari (School of Business, IPB University (SB-IPB), 2026)
Background: Digital Transformation has been observed to significantly enhance the supply chain operations of various SMEs across different sectors, and Supply Chain Competence is needed in businesses as this fosters the development and achievement of strategic goals capable of increasing Competitive AdvantagesPurpose: This study aimed to examine the influence of digital transformation (DT) and supply chain competence (SCC) on competitive advantage (CA) in small and medium enterprises (SMEs) in West Java, IndonesiaDesign/methodology/approach: In order to achieve the stated objective, a quantitative approach was adopted to examine the mediating role of SCC in the relationship between DT and CA. Accordingly, data analysis was conducted using Partial Least Squares in Structural Equation Modeling, which provided strong insights into the relationships between the dependent and independent variablesFindings/Result: The results confirmed that DT significantly influences both CA (T=4.159, p=0.000) and SCC (T=19.355, p=0.000), while SCC significantly affects CA (T=6.535, p=0.000). Importantly, SCC significantly mediated the DT–CA relationship (T=5.822, p=0.000), indicating that DT enhanced CA both directly and indirectly through SCC. Conclusion: This study extends the Resource-Based View (RBV) and Dynamic Capability Theory by demonstrating that SCC functions as a mediating dynamic capability linking DT to CA in SME contexts. For practitioners, SME managers should prioritize integrated digital supply chain strategies, while policymakers in developing economies should facilitate digital infrastructure and competence-building programs to strengthen SME competitiveness.Originality/value (state of the art): This study contributes to the literature by providing an integrated capability-based model that empirically tests SCC as a mediating mechanism between DT and CA among SMEs in a developing economy. While prior studies predominantly examined DT–CA linkages in large firms within developed economies, this research uniquely demonstrates how specific SCC dimensions customer focus and responsiveness serve as dynamic capabilities that translate DT investments into sustained CA for resource-constrained SMEs in West Java, Indonesia Keywords: digital transformation, supply chain competence, competitive advantage, SMEs